Evaluating the Impact of Servicescape and Information Systems on University Students’ Academic Performance in Malang - Nur Prima Waluyowati; Muhammad Hafiz Riandi (International Journal of Applied Business and International Management, 2025)
In the ever-changing world of higher education services, examining factors that impact students’ performance is important in making sure that student’s learning experience can be improved to reach academic success. This research investigates the impact of University Servicescape (USc) and Information Systems Implementation Quality (ISQ) on student performance in higher education institutions in Malang. USc refers to the physical environment and facilities provided by the university. At the same time, the ISQ pertains to the effectiveness and efficiency of the technological systems employed for academic and administrative purposes. Both factors have been deeply researched separately in the context of higher education service management, but no research has delved into both at the same time. A quantitative empirical survey-based study is employed to examine this topic. The sample consists of university students studying in Malang, East Java, Indonesia. The results empirically show that USc and ISQ significantly impact university student performance in higher education, particularly within institutions in Malang, East Java, Indonesia. These findings should be useful for policymakers, university administrators, and educators in enhancing the delivery of educational services in higher education institutions across Indonesia.